Pelatihan Manajemen Kepengawasan Koperasi bagi Pengawas Koperasi di Provinsi Sumatera Selatan - Yohanes Susanto; Luis Marnisah (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: This community service aims to provide knowledge and skills to cooperative supervisors. Research Methodology: In this service, we provided cooperative management materials, knowledge, and understanding to cooperative supervisors on their obligations and rights as cooperative supervisors using lecture, practice, and discussion methods. The understanding of the material was measured using a questionnaire before and after giving the material. Results: The results of the training have a positive and significant effect on the performance of cooperative supervisors, can increase the knowledge and understanding of cooperative supervisors in carrying out their main duties and functions as supervisors Conclusion: The implementation of this service, especially in fostering cooperative supervisors, is very useful. This is indicated by the results of the pre-test and post-test of the participants showing significant results. The supporting factors are the facilities for carrying out activities provided by the organizers and the inhibiting factor is that some of the participants do not have an economic background knowledge so it is quite difficult for them to understand cooperative finance.